Підвищення якості технології пресування твердосплавних породоруйнівних зубків у шарошки бурових доліт - Яким, Роман Степанович; Сліпчук, Андрій Миколайович (НТУ "ХПІ", 2017)
Встановлено, що за забезпечення існуючою технологією нормального розподілу розмірів отворів у вінцях шарошок під вставні твердосплавні зубки типорозміром 14 мм створюються сприятливі умови для групування селективних груп по розмірах отворів та вставних зубків. Запропоновано підхід для встановлення раціональних параметрів натягів для проектування з’єднання „зубок – шарошка” у дев’яти селективних групах. Такий підхід уможливлює забезпечити стале середнє значення натягу на рівні 0,103 мм. Формування селективних груп зубків і отворів під них забезпечує отримання заданої точності при складанні з’єднання „зубок – шарошка” за умов заданої точності оброблення отворів у вінцях шарошок. Це усуває виникнення нераціональних значень натягів, які знижують надійність з’єднання „зубок – шарошка”.

Determined that modern technology to ensure normal distribution sizes of holes in the roller cone bit for installation cutter pick under the false standard size of 14 mm create favourable conditions for selective grouping groups the size of holes and plug tungsten carbide inset cutter. In article proposed a method to establish rational parameters tensions in the design of connections "cone - tungsten carbide inset cutter" nine selective groups. This approach enables to provide constant average value of tension at 0.103 mm. Formation of selective groups tungsten carbide inset cutter and holes for it a specified accuracy when drawing up connection "cone - tungsten carbide inset cutter " provided the desired precision cutting holes in the row of cone. It does not appear irrational values of the tensions which reduce the reliability of "cone - tungsten carbide inset cutter ". The purpose of the article is to highlight research dedicated to solving important practical problems to improve the existing production technology of roller cone bit of embedded rock cutting equipment. The main task is studying the effect of design parameters connection "cone - tungsten carbide inset cutter". We solve this task in the case when tungsten carbide inset cutter diameter below 14 mm and investigate the impact of tensions to ensure the reliability of the embedded rock cutting equipment.
Refinement technology pressing of tungsten carbide inset cutter in roller cone bit
Keywords: вставні породоруйнівні зубки; натяг; з'єднання "зубок-шарошка"; селективна група; буріння; tungsten carbide inset cutter; tension; connection "cone - tungsten carbide inset cutter"; selective group; cone